1996
DOI: 10.1177/44.9.8773565
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the C-cell numbers in rat thyroid glands using the optical fractionator.

Abstract: We estimated the total number of calcitonin-immunoreactive C-cells in rat thyroid gland using the optical fractionator, the unbiased stereological method for estimation of numbers. It was necessary first to use a fiiative composed of formalin, acetic acid, and ethanol to distinctly visualize the C-cells. The 40-pm-thick sections had to adhere to chromalum-gelatin-coated Superfrost Plus glass slides, and the immunostaining technique had to stain the C-cells evenly throughout the whole sections. Because the C-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
2
5
1
1
Order By: Relevance
“…These differences were more noticeable in the group treated with EDP alone than in animals that received the combination of EDP and Ca. In contrast to the data of Feinstein et al (1996), a decreased number of these cells in the EDP-treated group correlates well with the reduced level of serum CT observed in these animals. The present data clearly demonstrate that chronic treatment with nearly physiological EDP doses, comparable with those previously used in human studies (Agnusdei et al 1990), acts by inhibiting both the structure and function of the C cells in middle-aged rat females.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…These differences were more noticeable in the group treated with EDP alone than in animals that received the combination of EDP and Ca. In contrast to the data of Feinstein et al (1996), a decreased number of these cells in the EDP-treated group correlates well with the reduced level of serum CT observed in these animals. The present data clearly demonstrate that chronic treatment with nearly physiological EDP doses, comparable with those previously used in human studies (Agnusdei et al 1990), acts by inhibiting both the structure and function of the C cells in middle-aged rat females.…”
Section: Discussioncontrasting
confidence: 63%
“…CT and CGRP-containing cells increased in number with age and reached a plateau at 18 months (Salih et al 1993). However, recent data of Feinstein et al (1996) showed that serum levels of CT and Ca were not closely correlated to the C cell number in adult rats. Having in mind discrepancies of the data obtained in humans and experimental animals, the present study employing histochemical, stereological, and biochemical methods, was focused on C cell structure and function of middle-aged female rats treated chronically, with estradiol dipropionate (EDP) and Ca given alone or in combination.…”
Section: Introductionmentioning
confidence: 91%
“…At the same time the number of C cells per unit area was increased, which may be generally explained as a compensatory response of this endocrine population for the prolonged lack of sex hormones. However, Feinstein et al (1996) suggested that C cell number was not closely correlated to the serum levels of CT and the reason for these results is not clear. In Ovx rats, Sakai et al (2000) found decreases in the number of thyroid C cells, the number of secretory granules in these cells, and the area occupied by the Golgi complex in comparison with control rats.…”
Section: Discussionmentioning
confidence: 93%
“…The hemispheres were placed in a container with the midsagittal surface facing down, embedded in blocks of paraffin and sectioned into coronal series of 40·m-thick sections on a Leica microtome (Fig.·1B,C). Satisfactory adhesion of the thick sections to glass slides was obtained using Superfrost Plus glass slides primed with a chromalun-gelatin solution (Feinstein et al, 1996). A predetermined fraction of the 40·m-thick sections was sampled using moist filter paper and carefully rolled onto 40°C preheated primed slides covered by a thin layer of distilled water.…”
Section: Tissue Processingmentioning
confidence: 99%